2018
DOI: 10.1186/s12951-018-0356-z
|View full text |Cite
|
Sign up to set email alerts
|

Memantine loaded PLGA PEGylated nanoparticles for Alzheimer’s disease: in vitro and in vivo characterization

Abstract: BackgroundMemantine, drug approved for moderate to severe Alzheimer’s disease, has not shown to be fully effective. In order to solve this issue, polylactic-co-glycolic (PLGA) nanoparticles could be a suitable solution to increase drug’s action on the target site as well as decrease adverse effects. For these reason, Memantine was loaded in biodegradable PLGA nanoparticles, produced by double emulsion method and surface-coated with polyethylene glycol. MEM–PEG–PLGA nanoparticles (NPs) were aimed to target the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(113 citation statements)
references
References 47 publications
6
99
0
Order By: Relevance
“…Poly(ethylene glycol)-b-poly(lactide-co-glycolide) (PEG-b-PGLA) seems to be a promising DDS [120][121][122], capable of passing the blood brain barrier [123,124]. Liu et al [125] investigated PEG 2000 / 5000 -b-PLGA (different ratio's) micelles on their biocompatibility and indicated that all micelles presented very low cytotoxicity.…”
Section: Peg-b-plgamentioning
confidence: 99%
“…Poly(ethylene glycol)-b-poly(lactide-co-glycolide) (PEG-b-PGLA) seems to be a promising DDS [120][121][122], capable of passing the blood brain barrier [123,124]. Liu et al [125] investigated PEG 2000 / 5000 -b-PLGA (different ratio's) micelles on their biocompatibility and indicated that all micelles presented very low cytotoxicity.…”
Section: Peg-b-plgamentioning
confidence: 99%
“…Polymeric nanoparticles can be obtained from natural, semi-synthetic or synthetic polymers (e.g., chitosan [37][38][39], polylactic acid (PLA), poly(lactic-co-glycolic acid) (PLGA) [40][41][42][43]), which will then govern the way the drugs are encapsulated inside the matrix (dissolved or dispersed) or attached onto the nanoparticle' surface (chemically bound or adsorbed), and how the drug is released [44]. Polymeric nanoparticles can be produced with a variety of sizes and shapes, with high drug payload for both hydrophilic and lipophilic molecules, can be surface-modified to increase the plasma half-life (e.g., PEGylation [45,46]) to have site-specific targeted delivery [47], and release the drug in a controlled fashion [48][49][50].…”
Section: Production Methods Of Clinically Compliant Nanopharmaceuticsmentioning
confidence: 99%
“…Decreased amyloid-beta (Aβ) plaques and related inflammation characteristics [117] mPEG-PLGA Schisantherin A Improved oral bioavailability, increased brain uptake, and enhanced the bioactivity of this drug [118] Rabies virus glycoprotein 29-modified deferoxamine-loaded PLGA…”
Section: Doxorubicin (Dox) and Loperamidementioning
confidence: 99%
“…These polymeric NPs can target brain cancer and other diseases [195,196]. Sanchez-Lopez et al developed PLGA PEGylated NPs for the delivery of memantine in AD [117]. MTT tests showed that these NPs are safe for brain cell lines (bEnd.3 and astrocytes) and PLGA PEGylated NPs could penetrate the BBB.…”
Section: Plgamentioning
confidence: 99%